The historical narrative of Taiwan folk song movement as student cultural production - Chi Wan; Xiaohua Zhu (Discover Global Society, 2024)
Abstract Scholars have concerned with the possibilities of the independent cultural production in the educational field. In the schools, the educated are surrounded by the powerful diverse cultural influences. Those have been discussed in different issues from sociological, anthropological and semiotic perspectives. In fact, there is a gap between theoretical and practical research in cultural studies. Therefore, it’s necessary to explore the production and educational significance of student culture from the perspective of specific culture event. This paper chooses Taiwan folk song movement as a specific Chinese cultural event occurred in the mid-1970s to the early 1980s. It can be named as “student soundscape” because it is created by the high school and the college students. The slogan of this movement “Sing Our Own Songs” was initially to question the students’ cultural dependency on western pop music and the stereotype of Chinese urban songs named as “Era Music”. It is the ordinary students who seek for a cultural turn- a new native art form with authentic common experience. With their humanism ideal and complicated affection, emphasized as “nostalgia”, this generation of youth have experienced a trip in search for cultural roots and developed a cultural renaissance age.